Food Production and Global Environmental Change: Stewardship as a Guiding Principle for Christian Development Organizations - Stoep, Jan van der; van Nieuw Amerongen, Maarten; Treuren, Antonie (2025)
Providing food security has traditionally been an important motive for development cooperation. At the same time, agriculture also has a major impact on the environment, which in turn threatens food production itself. This article argues that the tension between food production and global environmental change is largely caused by a modern dualism that pits man and nature, donor and recipient, and modernity and tradition against each other. It explores whether stewardship can help Christian NGOs find a way forward. Stewardship is closely linked to a Christian view of the relationship between man and earth and the relationship of people to each other. However, it is not uncontroversial. Therefore, a reinterpretation of the concept is needed. Finally, three principles are discussed that derive from a renewed vision of stewardship and can provide strategic direction: working together with nature, empowering local communities and adaptive transformation. Stewardship does not offer ready-made solutions, but that is precisely its strength. It appeals to practical wisdom. Every context is different and requires its own balance of values and interests.
Keywords: development cooperation; Agriculture; Stewardship; faith-based organizations; Climate Change; Food Security